Empowerment of PKK Members in Utilizing Fragrant Lemongrass Oil as a Floor Cleaner Production Material in Sukasari Village, Seluma Regency, Bengkulu Province, 2023 - Krisyanella; Meinisasti, Resva; Khasanah, Heti Rais; Pudiarifanti, Nadia; Susilo, Avrilya Iqoranny; Muslim, Zamharira; Baharyati , Delta; Irnameria, Dira (CV Media Inti Teknologi, 2024)
The purpose of this activity is to increase the knowledge and skills of PKK members in Sukasari village in developing products from lemongrass oil. This can increase the selling value of lemongrass oil that has been produced, so that it can increase community income. The methods used were socialization, demonstration and self-assistance in making cleaners, packaging and labeling fragrant lemongrass floor cleaner products. At the socialization stage, participants received material and there was a discussion session. Participants were given a questionnaire to see their level of understanding of the material provided. After the participants were given counseling and demonstrations of product making, it was seen that there was an increase in the knowledge and skills of the participants in making these products independently. Also, it was seen that participants were interested in developing this product into a commercial product. The conclusion of this activity is that participants are able to produce this product independently. This product will be used for personal household needs and developed by the local BUMDes to become a commercial preparation.